Electro-Hydraulic Proportional System Real Time Tracking Control Development Based on Pulse width Modulation Method - Ezz Eldin Ibrahim; Tarek Elnady; Mohamed Saffaa Hassan; Ibrahim Saleh (Communications - Scientific letters of the University of Zilina, 2021)
The presented work was directed to develop the dynamic performance of an electro-hydraulic proportional system (EHPS). A mathematical model of the EHPS is presented using electro- hydraulic proportional valve (EHPV) by Matlab-Simulink, which facilitates the simulation of the hydraulic behavior inside the main control unit. Experimental work is done and the closed loop system is designed using the linear variable displacement transducer sensor (LVDT). The controller of the system is an Arduino uno, which is considered as a processor of the system. The model is validated by the experimental system. The study also presents a real time tracking control method, based on pulse width modulation, by controlling the speed of the actuator to achieve the position tracking with minimum error and low transient time, by applying the constant input signal 50mm the transient time was 0.9 seconds and the error 1.8%.